A Rare Case of Panton-Valentine Leukocidin-Related Cervical Empyema - Le, Hung; Nguyen, Dung Le Thuy; Ton, My Nu Tra; Phan, Duy; Tran, Anh Hoang Ngoc; Truong, Van Tri (Asian Journal of Neurosurgery, 2023)
Staphylococcus aureus is found in the normal skin and mucosa of approximately 30% of healthy populations and is the most common pathogen in human disease associated with bacteria. They are divided into methicillin-sensitive S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA). The S. aureus strains carrying the Panton-Valentine leukocidin genes (SA-PVL) were initially believed to belong to the MRSA group; however, recent reports showed they also belonged to the MSSA group (MSSA-PVL). SA-PVL is common in skin and soft-tissue infections but rare in musculoskeletal infections, especially in spondylodiscitis. We are reporting a case suffering from cervical spondylodiscitis and epidural abscess associated with MSSA carrying the Panton-Valentine leukocidin genes.
Keywords: cervical empyema; leukocidin; MSSA; spine surgery; Panton-Valentine; Staphylococcus aureus